Peran Komite Perlindungan dan Pemenuhan Hak-Hak Penyandang Disabilitas Daerah Istimewa Yogyakarta dalam Perlindungan Hukum bagi Perempuan Disabilitas Korban Kekerasan - Irawan, Andrie (UIR Law Review, 2018)
The promulgation of the Regional Regulation of Special Region of Yogyakarta Number 4 of 2012 on the Protection and Fulfillment of the Rights of Persons with Disabilities where one of the mandate of the Regional Regulation is with the establishment of the Fulfillment Committee and the protection of the rights of Disability of Special Region of Yogyakarta. The existence of the committee is a breakthrough and positive response from the local government to the problems of people with disabilities that occurred in Yogyakarta Special Region, one of them related to cases of violence that often occur against women with disability. So this paper would like to see the real role of the Special District Disability Committee of Yogyakarta especially in the case of legal protection for women disability victims of violence which hope not only the concrete role of the committee, as it is a newly born regional institution but also as success story on the partisanship of Regional Government Yogyakarta Specialties to Persons with Disabilities.